COMPETÊNCIAS GERENCIAIS NA INSTITUIÇÃO PÚBLICA DE ENSINO: UMA ANÁLISE DO DISCURSO DO GRUPO DE TRABALHO DE SUPERVISÃO EDUCACIONAL - SILVA, ANDRÉ LUIS DA (2019)
This study aimed to identify the managerial competences composed of knowledge, ability and attitude, from the perspective of pedagogical educational supervisors, project coordinators and the physical space manager, in a state institution of professional and technological teaching in the great ABC. In the current economic, political, and social context, in higher education and in vocational and technological training, managerial competencies are not a choice, but a condition that demands from the people management area of these organizations new strategies focused on their programs development and improvement of the managerial skills required of their servers, enabling them to cope with uncertain, dynamic and complex situations. The question that guides this study is: how do managerial competencies manifest in the pedagogical educational supervision-working group in the institution of vocational and technological education in Grande ABC, according to the report of its managers? To answer this question, the references were the studies of the theoreticians McClelland (1973) and Boyatizis (1982), who represent the American current, Le Boterf (2002) and Zarifian (2012), who belong to the French current, and Gonczi 1999) that is representative of the integrative current, besides other contemporary authors. The methodology used in this study was qualitative, with the use of the interview as an instrument applied in the analysis of the speeches of the six professionals that are part of the management process of the pedagogical management of IEEPT. The results showed that the elements of knowledge, ability and attitude of the SE, CPs and the GEF are present. In addition, the managerial skills of these professionals were evidenced, among them, they point out five main ones that are orientation, leadership, ethics, constant learning and technical knowledge. Also, it was possible to verify special managerial competences, such as "passion" and "emotional balance". In short, the adoption of managerial skills by people management directs higher education and professional institutions to achieve value through superior performance in managerial processes, in the relationships of their actors and in the delivery of quality education to society generally.